2013
DOI: 10.1002/gps.3929
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender and age on cognitive inhibition in late‐onset depression: a case‐control study

Abstract: Cognitive inhibition impairment, and more specifically its attention component, was the main characteristic of depression in the studied sample of older adults, independently of gender and age of depression onset. It is essential to perform similar studies in both genders in view of future tailor-made therapeutic modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
3
6
1
Order By: Relevance
“…In our previous study , we found that the BVMT-R was among the tests that showed the least sensitivity to cognitive side effects from T1 to T2. Our results are in line with previous studies of patients with geriatric depression reporting weak results on the inhibition part of the Stroop test (Richard-Devantoy, Deguigne, Annweiler, Letourneau, & Beauchet, 2013), as well as on the TMT B (King, Cox, Lyness, & Caine, 1995). A slow processing speed has been pointed out as a confounder of the validity of the BVMT-R (Tam & Schmitter-Edgecombe, 2013) as a measure of memory.…”
Section: Neurocognitive Assessmentsupporting
confidence: 93%
“…In our previous study , we found that the BVMT-R was among the tests that showed the least sensitivity to cognitive side effects from T1 to T2. Our results are in line with previous studies of patients with geriatric depression reporting weak results on the inhibition part of the Stroop test (Richard-Devantoy, Deguigne, Annweiler, Letourneau, & Beauchet, 2013), as well as on the TMT B (King, Cox, Lyness, & Caine, 1995). A slow processing speed has been pointed out as a confounder of the validity of the BVMT-R (Tam & Schmitter-Edgecombe, 2013) as a measure of memory.…”
Section: Neurocognitive Assessmentsupporting
confidence: 93%
“…Our results expand those preliminary indications, suggesting that women with depression have more severe impairment than men, across multiple cognitive domains, even in the absence of psychotic symptoms. The other three published studies on this topic, which did not find sex differences in neuropsychological measures, are not comparable to ours as they investigated different cognitive domains such as attention and cognitive inhibition [23] or they addressed emotional aspects of cognitive functioning, namely emotional working memory [24] and autobiographical memory recall [25].…”
Section: Discussioncontrasting
confidence: 69%
“…We investigated the influence of gender on neuropsychological performance in a sample of inpatients with current MDD without psychotic features who were hospitalized for a psychiatric rehabilitation program. Previous findings regarding the differences in cognitive function between men and women with depression are scant, mixed, and insufficient to draw conclusions [23][24][25][26].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nonetheless, MDD subjects seem to display a wide range of cognitive deficits -ranging from no impairment to extreme impairment -depending on the effect of different factors, such as age (Herrmann et al, 2007), gender (Richard-Devantoy et al, 2013), education level (Elgamal et al, 2007), recurrence of episodes (Gorwood et al, 2008), symptom severity (McClintock et al, 2010) and antidepressant treatment (Rosenblat et al, 2015). The study of cognitive performance in MDD is made even more complex by the fact that different depressive subtypes, such as psychotic, atypical and melancholic features, have shown specific effects on cognition (Exner et al, 2009;Fleming et al, 2004;Lin et al, 2014;Markela-Lerenc et al, 2006;Michopoulos et al, 2008;Pier et al, 2004;Quinn et al, 2012a;Quinn et al, 2012b;Roca et al, 2015;Rush et al, 1983;Withall et al, 2010;Zaninotto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%